2010
DOI: 10.1053/j.ajkd.2010.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Cognitive Function in Maintenance Hemodialysis Patients

Abstract: Background Both depression and cognitive impairment are common in hemodialysis patients, are associated with adverse clinical outcomes, and place an increased burden on health care resources. Study Design Cross-sectional cohort Setting & Participants 241 maintenance hemodialysis patients in the Boston area Predictor Depressive symptomatology, defined by a Center for Epidemiological Studies Depression Scale (CES-D) score of 16 or higher Outcome Performance on a detailed neurocognitive battery Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
89
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(103 citation statements)
references
References 52 publications
10
89
0
4
Order By: Relevance
“…Similar high levels of psychiatric morbidity in critically ill patients have been found by other authors [15]. Among patients receiving haemodialysis for end-stage renal disease, symptoms of anxiety and depression are common, with 45.7% of subjects meeting criteria for an anxiety disorder [16] and 23.7% with significant depressive symptoms [17]. Symptoms consistent with post-traumatic stress are also common in this patient [11] assessed QoL in survivors of critical illness with AKI across ten centres in Finland, using the EuroQol-5D (EQ-5D) questionnaire.…”
Section: Discussionsupporting
confidence: 80%
“…Similar high levels of psychiatric morbidity in critically ill patients have been found by other authors [15]. Among patients receiving haemodialysis for end-stage renal disease, symptoms of anxiety and depression are common, with 45.7% of subjects meeting criteria for an anxiety disorder [16] and 23.7% with significant depressive symptoms [17]. Symptoms consistent with post-traumatic stress are also common in this patient [11] assessed QoL in survivors of critical illness with AKI across ten centres in Finland, using the EuroQol-5D (EQ-5D) questionnaire.…”
Section: Discussionsupporting
confidence: 80%
“…Depressive affect can directly influence poor adherence to diet and fluid regimens (16). Furthermore, chemical brain alterations in depressed patients may affect cognitive dysfunction (which may manifest as poor adherence) (17), and cognitive dysfunction has been associated with depressive affect in HD patients (18). Poor adherence may also extend to missed HD treatments, which has been associated with greater risk for hospitalization from not just cardiovascular causes but all-causes as well (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that neuropsychological measures used in this study did assess cognitive and psychomotor domains found to be particularly impaired in ESRD patients on maintenance HD such as memory, mental efficiency, psychomotor speed, attention, and executive function [2,5,6,7,26,27]. …”
Section: Discussionmentioning
confidence: 99%